Public Opinion Formation in the Digital Age : A Review of Literature - Diah Fatma Sjoraida; Bucky Wibawa Karya Guna; Aat Ruchiat Nungraha; Daniel Pasaribu; Novianty Djafri (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The digital age has brought significant changes in the way people access and process information. Social media and other online platforms have become a major source of information and public opinion. This study aims to review the literature on public opinion formation in the digital age. This study uses the literature review method to analyze literature relevant to the research topic. A literature review shows that the digital age has had a significant impact on the formation of public opinion. Social media and other online platforms have become the primary means for individuals to access information, share ideas, and exchange opinions. This has led to changes in the way public opinion is formed and disseminated. The formation of public opinion in the digital age is a complex and dynamic phenomenon. Social media and other online platforms have an important role to play in shaping public opinion. A better understanding of the process of forming public opinion in the digital age is needed to develop effective communication strategies and build a more democratic society.